Does Financial Development Lower Energy Intensity in India? - M. Tamilselvan; Srinivasan Palamalai; S. Manikandan; Manjula Veerabhadrappa; Vinod Repalli (International Journal of Energy Economics and Policy, 2022)
Although the relationship between finance and growth is gaining significant attention, little is known about how financial development indicators affect energy intensity in emerging nations. Given the complexity of the growth effects of financial development and energy intensity dynamics, the present paper investigates the effect of financial development and economic growth on energy intensity in India using Autoregressive Distributed Lag (ARDL) bounds testing approach. The result indicates that financial development indicators and economic growth had a long-run relationship with energy intensity. Besides, the empirical results reveal that financial development and economic growth had a negative and significant impact on energy intensity in the short and long-run, inferring that financial development and economic growth lower energy intensity in the country. The findings are helpful for India's policymakers in order to maintain the complementarity between financial development and energy intensity.